Naked Mole-Rat Social Phenotypes Vary in Investigative and Aggressive Behavior in a Laboratory Partner Preference Paradigm - Toor, Ilapreet; Maynard, Rashoun; Peng, Xinye; Beery, Annaliese K.; Holmes, Melissa M. (Frontiers in Ecology and Evolution, 2022)
Here we employ the partner preference test (PPT) to examine how naked mole-rat non-breeding individuals of different behavioral phenotypes make social decisions. Naked mole-rats from six colonies were classified into three behavioral phenotypes (soldiers, dispersers, and workers) using a battery of behavioral tests. They then participated in a 3 hour long PPT, where they could freely interact with a tethered familiar or tethered unfamiliar conspecific. By comparing the three behavioral phenotypes, we test the hypothesis that the PPT can be used to interrogate social decision-making in this species, revealing individual differences in behavior that are consistent with discrete social phenotypes. We also test whether a shorter, 10 minute version of the paradigm is sufficient to capture group differences in behavior. Overall, soldiers had higher aggression scores towards unfamiliar conspecifics than both workers and dispersers at the 10 minute and 3 hour comparison times. At the 10 minute comparison time, workers showed a stronger preference for the familiar animal’s chamber, as well as for investigating the familiar conspecific, compared to both dispersers and soldiers. At the 3 hour time point, no phenotype differences were seen with chamber or investigation preference scores. Overall, all phenotypes spent more time in chambers with another animal versus being alone. Use of the PPT in a comparative context has demonstrated that the test identifies species and group differences in affiliative and aggressive behavior towards familiar and unfamiliar animals, revealing individual differences in social decision-making and, importantly, capturing aspects of species-specific social organization seen in nature.